The use of Virtual Reality on Writing Performance at MTsN Batu - Siti Sudaryani; Diah Ambarumi Munawaroh (JEET, Journal of English Education and Technology, 2023)
This scientific article explores the use of virtual reality (VR) technology in improving students' writing skills, specifically descriptive text writing at MTsN 1 Batu. The study aims to determine the effectiveness of VR technology in enhancing students' writing skills and to identify the challenges encountered in using VR technology in the classroom. The research methodology employed in this study is a quasi-experimental design, with a pre-test and post-test control group. The participants are 60 students from MTsN 1 Batu, divided into two groups: the experimental group and the control group. The experimental group received VR-based writing instruction, while the control group received traditional writing instruction. The data collected from pre-tests and post-tests were analyzed using t-test. The findings indicate that the use of VR technology in teaching descriptive text writing significantly improved students' writing skills. Furthermore, the experimental group outperformed the control group in terms of the quality of their descriptive text. The study also reveals several challenges in using VR technology in the classroom, such as technical problems, time constraints, and students' unfamiliarity with VR technology. These challenges can be overcome through proper planning, training, and technical support. In conclusion, this study suggests that the use of VR technology can be an effective tool for improving students' writing skills, particularly in descriptive text writing. However, it requires careful planning and implementation to overcome the challenges encountered in using VR technology in the classroom. The study's implications are significant for educators, as it highlights the potential of VR technology in enhancing students' learning experience.